2021
DOI: 10.1021/acs.orglett.1c01110
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Resolution of Tertiary Allylic Alcohols: Highly Enantioselective Access to Cyclic Ethers Bearing an α-Tetrasubstituted Stereocenter

Abstract: A chiral phosphoric acid-catalyzed kinetic resolution of tertiary allylic alcohols was developed to provide structurally valuable enantioenriched 2,2-disubstituted tetrahydrofurans, tetrahydropyrans, and oxepane. A variety of tertiary allylic alcohols were resolved with selectivity factors of ≤120. A tertiary allylic carbocationic intermediate mediates the enantioselective intramolecular substitution to achieve high regio- and enantioselectivity. A gram-scale reaction with low catalyst loading and subsequent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Encouraged by this remarkable improvement in the enantioselectivity, the 18 O -labeling experiment was also carried out to reconfirm the “OH as nucleophile” mechanism, and the cyclization of 18 O - 1a using ( S )-BNDHP (5 mol %) yielded 2a with the naturally abundant 16 O -containing ring in 97% crude 1 H NMR yield [ESI-TOF (pos): C 12 H 15 NO:C 12 H 15 N 18 O (98:2)] (SI page S23). These results again corroborate our two-step mechanism involving the decay of TAP- 1 followed by retentive cyclization using CCP/PP, as well as inspiring us to continue our research on the library of seven-membered phosphorus-heterocycle variants (BPAs) and their phenotypes for the exclusively retentive cyclization of N -(2-hydroxylethyl)­amides.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Encouraged by this remarkable improvement in the enantioselectivity, the 18 O -labeling experiment was also carried out to reconfirm the “OH as nucleophile” mechanism, and the cyclization of 18 O - 1a using ( S )-BNDHP (5 mol %) yielded 2a with the naturally abundant 16 O -containing ring in 97% crude 1 H NMR yield [ESI-TOF (pos): C 12 H 15 NO:C 12 H 15 N 18 O (98:2)] (SI page S23). These results again corroborate our two-step mechanism involving the decay of TAP- 1 followed by retentive cyclization using CCP/PP, as well as inspiring us to continue our research on the library of seven-membered phosphorus-heterocycle variants (BPAs) and their phenotypes for the exclusively retentive cyclization of N -(2-hydroxylethyl)­amides.…”
Section: Resultssupporting
confidence: 76%
“…Mechanistic studies on a model reaction revealed that the decomposition of TAP- 1 provides the catalyst CCP, which subsequently catalyzes the cyclization of the N -(2-hydroxyethyl)­amides. Organophosphorus-based molecular design represents thus a useful strategy for asymmetric catalysis , and for the further development of catalytic dehydration reactions involving alcohols, amides, and/or carboxylic acids…”
Section: Discussionmentioning
confidence: 99%
“… 7 In the methodologies reported for the KR of racemic tertiary alcohols in recent years, chiral phosphoric acids (CPAs), which are one of the most powerful and privileged organocatalysts employed in a broad range of enantioselective transformations, 10 have proven to be excellent catalysts. 8 Several reaction systems, such as acetalization, 8 a – c transesterification, 8 d condensation, 8 e enamine/imine tautomerization, 8 f and S N 1-type reaction, 8 g have been established in a highly resolved manner using CPAs as the efficient chiral Brønsted acid catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the catalytic KR of racemic secondary alcohols, 4 reliable methods for the non-enzymatic KR of tertiary alcohols remain few. 5–9 Several groups have reported the use of chiral Lewis base (nucleophilic) catalysts 6 and chiral transition metal catalysts. 7 In the methodologies reported for the KR of racemic tertiary alcohols in recent years, chiral phosphoric acids (CPAs), which are one of the most powerful and privileged organocatalysts employed in a broad range of enantioselective transformations, 10 have proven to be excellent catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…6 Mao and coworkers uncovered a chiral phosphoric acid-catalyzed kinetic resolution reaction of tertiary allylic alcohols. 7 Recently, Zhao and co-workers explored a new type of chiral Brønsted acidcatalyzed asymmetric allylic amination (eq 2, Scheme 1b). 8 Despite these important advances, the organocatalytic allylic substitutions are largely limited to the employment of relatively reactive benzyl and tertiary alcohols.…”
mentioning
confidence: 99%